THE ROLE OF STATE-OWNED ENTERPRISES AS DEVELOPMENT AGENTS IN PROMOTING SUSTAINABLE ECONOMIC GROWTH: A LITERATURE REVIEW OF GOVERNMENT POLICY, OPERATIONAL EFFICIENCY, AND THE CHALLENGES OF GLOBALISATION - Ignatius Septo Pramesworo; Mohamad Khairi Bin Haji Othman (Adisam Publisher, 2025)
This study examines the role of State-Owned Enterprises (SOEs) as development agents in promoting sustainable economic growth in Indonesia. The literature review focuses on analysing government policies that shape the operational framework of SOEs, operational efficiency as a key factor in improving performance, and the challenges faced in a dynamic and competitive era of globalisation. The results of the study indicate that synergy between supportive policies, internal efficiency, and adaptation to global pressures is crucial to the success of SOEs in carrying out their strategic functions. The transformation of SOEs towards professional and sustainable governance will strengthen their contribution to creating inclusive, equitable, and environmentally friendly economic growth. Policy recommendations are suggested to balance the socio-economic role of SOEs while enhancing global competitiveness through innovation and good governance.